The Role of Risk Tolerance in Linking Psychological Biases and Financial Literacy to Gen Z Stock Trading Frequency - M Zaenal Efendi; Fitriyah Fitriyah (Universitas Muhammadiyah Sorong, 2026)
Positioning risk tolerance as a mediating variable, this study investigates the extent to which overconfidence, optimism bias, and financial literacy shape stock trading frequency among Generation Z investors in Malang City. A quantitative approach with an explanatory design was employed, with purposive sampling used to select 100 respondents. Data were gathered through a questionnaire instrument and subsequently analyzed using SmartPLS 4.0 software via SEM-PLS method. The results indicate that overconfidence, optimism bias, and financial literacy all bear a positive and significant influence on risk tolerance. Interestingly, not one of these three variables was found to produce a direct effect on stock trading frequency. Risk tolerance was demonstrated to serve as a full mediator in the relationship between the independent and dependent variables, while at the same time yielding a significant positive effect on trading frequency. These findings point to the conclusion that the trading behavior of Generation Z investors in Malang City is governed far more by their individual level of risk tolerance than by psychological or cognitive factors operating in isolation.